Public Private Partnership: A Strategy for Enhancing Access to Quality Education in Special Needs Education in Nigeria. - Abdulbaki , Rabiu Abdulkadir (International Journal of Educational Management, 2021)
The rationale for establishing Public-Private Partnerships (PPPs) in special needs education is revolving around maximizing the potential and expanding equitable access to schooling as well as improving qualitative education outcomes to individual with disabilities. This paper clarified the concepts of special needs education, exceptional learners, access to quality education for exceptional learners and most importantly examined the need for encouraging public-private partnerships with special needs education to augment government’s limited capacity and thus expand other private organizations support to the special needs education sector through philanthropic activities and high engagement ventures. However, the paper recommended that while partnering with private sectors, government should emphasized on the provision of appropriate physical resources such as buildings, classrooms, resource rooms, library facilities, laboratories, game activities, audio-visual centers, which are stimulating and conducive to learning and above all avoiding architectural barriers should be a priority in order for exceptional learners enjoy easy access to the learning environment, among others.